Analisis Desain Turbin Air Tipe Aliran Silang (Crossflow) dan Aplikasinya di Desa Were I Kabupaten Ngada-NTT - Verdy Ariyanto Koehuan; Agustinus Sampealo (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2015)
ABSTRACT Utilization of water energy potential for the development of hydroelectric power generation systems, especially the use of crossflow type water turbine applications include virtually any location with water flow rate and high head or falling water is low and medium. This type of water turbine performance can be known through the analysis of the turbine runner and the steering nozzle turbine inlet flow and a series of tests in the field. Turbine characteristics to changes in water flow, high water fall (head), angle of attach falling water, and the flow velocity in the runner can be known, and then the application becomes more optimal. With a head of 15 m and and discharge available 230 liters/s, do the design parameters of the length and diameter of the runner, can be obtained specific speed of 47.931 rpm for water discharge 0.1261 m3/s. Dimensional turbine runner DA, (L=15 cm) and (D1=15 cm), turbine efficiency is obtained 88.74 % yield effective power of Pe (16.466 kW). While the dimensions of the turbine runner DB, (L=20 cm) and (D1=20 cm), can be obtained specific speed of 55.346 rpm for the flow rate Q (0.1681 m3/s), and the efficiency of 88.74 % effective at generating power Pe (21.954 kW). The results of the analysis parameters for turbine runner diameter (D1) 15 cm with DA turbine runner length (L=15 cm) to the turbine DB (L=20 cm) showed increase in the flow rate and the effective power as well as 25 %, but the rotation and turbine efficiency does not change.